EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE QUESTION STUDENTS HAVE (QSH) TERHADAP HASIL BELAJAR IPA SISWA KELAS VII SMP NEGERI 11 YOGYAKARTA - Ica Ningsih; Hidayati Hidayati; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
This study aims to determine the effectiveness of cooperative learning model quetion Students Have (QSH) on learning outcomes IPA. The method used is the quasi-experimental method. This research was conducted at the Junior High School 11 Yogyakarta 2014/2015 school year involving 66 students of class VII, namely class VIIB and VIID. Collecting data using the documentation techniques and engineering tests. The results were obtained data showing the value t of t-test was done, tvalue greater than the value ttable 1 % (2,752 > 2,660), thus it can be concluded that cooperative learning model Question Students Have (QSH) is more effective in learning science compared with expository learning.